From the Editor: What? You're a human, too?!. (1st September 2022) - Kelly, Rob
Abstract : As you read this latest rant, I am preparing my talk for the Gordon Research Conference (GRC) on Aqueous Corrosion, chaired this year by the illustrious Jamie Noël of Western University (see more about him in People News).